STRATEGI TRANSFORMASI DIGITAL DALAM INOVASI PERENCANAAN PENDIDIKAN ISLAM UNTUK MENINGKATKAN MUTU PENDIDIKAN - Rahmah; Ahmad Salabi; Yahya Mof (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The rapid growth of digital technology has brought significant changes to the field of education, including the planning system of Islamic education. Islamic educational institutions are required to adapt to technological developments so that educational management can run more effectively and in accordance with current needs. Digital transformation has become an important step in creating educational innovation that can improve the quality of Islamic education. This study aims to determine digital transformation strategies in the innovation of Islamic education planning and their impact on improving educational quality. This research uses a library research method with a qualitative descriptive approach. The data were collected from various scientific journals, books, and academic articles related to digital transformation and Islamic education. The results show that the use of digital technology such as Learning Management Systems (LMS), e-learning, and educational information systems can help Islamic educational institutions improve administrative effectiveness, communication, and learning processes. In addition, the use of digital technology also makes learning more flexible and interactive. However, the implementation of digital transformation still faces several obstacles, such as limited technological facilities and low digital competence among educators. Therefore, appropriate strategies are needed through human resource development and the provision of technological facilities so that digital transformation can be implemented properly.